Pentas Jihad Gerakan Salafi Radikal Indonesia - Wahid, Din (Studia Islamika, 2007)
This book is largely based on the writer's PhD thesis completed at Utrecht University in the Netherlands. This book represents an in-depth study of Laskar Jihad. Laskar Jihad has become somewhat prominent in recent times namely because of its role in the bloody conflict in Ambon. This religious conflict between Christians and Muslims resulted in countless casualties on both sides. The author takes the view that the phenomenon of Laskar Jihad represents a kind of synthesis between Islamic doctrine, militancy and efforts to strengthen the identity of a group that felt sidelined by modernization. Laskar Jihad's involvement in the conflict in Ambon was supported by - amongst others - fatwas from Salafi scholars in the Middle East (Mecca, Medina and Yemen).DOI:Â 10.15408/sdi.v14i2.552